Patient satisfaction with inpatient psychiatric treatment and its relation to treatment outcome in unipolar depression and schizophrenia. (June 2015) - Köhler, Stephan; Unger, Theresa; Hoffmann, Sabine; Steinacher, Bruno; Fydrich, Thomas
Abstract: Objects. Patient satisfaction with psychiatric treatment has emerged as an important factor with respect to the quality of health care. Methods. Patient satisfaction using the Zurich Satisfaction Questionnaire (ZUF-8) as well as symptom severity (measured with the Hamilton Depression Scale [HRSD], Brief Psychiatric Rating Scale and Clinical Global Impression Scale) was assessed at admission and discharge of inpatient treatment in patients with a major depressive episode (MDD, N = 217) and schizophrenia ( N = 75). Differences between the two diagnostic groups (using T-tests) and correlations of patient satisfaction with different social and treatment variables were calculated (Pearson product-moment correlation). Results. The mean score of patient satisfaction was 26.8 points (ZUF-8; range 8–32 points), without differences between MDD and schizophrenia ( t = 0.45, p = 0.78). Patients with MDD and personality disorder showed lower satisfaction than patients with MDD without personality disorder ( t = 2.31, p = 0.03). Patient satisfaction correlated negatively with severity of depressive symptoms at discharge (HRSD: r = − 0.38; p < 0.01) and number of comorbidities ( r = − 0.42; p < 0.01) in MDD. Number of prescribed drugs correlated negatively with patient satisfaction in both groups (depression: r = − 0.28, p = 0.02; schizophrenia: r = − 0.24; p = 0.03). Conclusions. Patient satisfaction was high without differences between MDD and schizophrenia. Severity of disease and comorbidites in MDD and number of prescribed drugs in both groups were related with reduced patient satisfaction.